Instrumentos alternativos para aulas práticas de Química no ensino remoto para alunos do 1º Ano do Ensino Médio - FRANCO, Anderson Rogério Beltrão (2022)
The present work discusses the results of a research - action carried out in a class of the 1st year of High School, whose objective was to present alternative instruments so that they can be used in the teaching of Chemical Reactions, aiming to help teachers in the process of re-elaboration of experimental activities , adapting them for remote teaching, due to the COVID-19 pandemic. Therefore, this study was developed with low-cost and easily acquired materials. To facilitate the dialogue with students, the experiments were carried out via Google Meet. Questionnaires were applied to quantify the research result. Through the analysis of the applied questionnaires, it was noticed the understanding of the subject and participation in the classes. In view of this, it appears that experimental activities during remote teaching are an important tool in the teaching-learning process in Chemistry classes.